Synergistic effects of micro-/nano-fillers on conductive and electromagnetic shielding properties of polypropylene nanocomposites. Issue 2 (25th January 2018) - Li, Ting-Ting; Chen, An-Pang; Hwang, Po-Wen; Pan, Yi-Jun; Hsing, Wen-Hao; Lou, Ching-Wen; Chen, Yueh-Sheng; Lin*, Jia-Horng
ABSTRACT: This study presents the synergistic effects of graphene nanosheets (GNSs) and carbon fibers (CFs) additions on the electrical and electromagnetic shielding properties of GNS/CF/polypropylene (PP) composites. These composites were fabricated by the melt blending of different ratios of GNSs and CFs (20:0, 15:5, 10:10, 5:15 and 0:20 wt/wt%) into a PP polymer matrix using a Brabender mixer. Besides, the chemical and crystalline structures and the thermal stability of the resultant GNS/CF/PP composites were characterized by Fourier transform infrared (FT-IR) spectroscopy, X-ray diffraction (XRD) and thermogravimetric analysis (TGA). FT-IR and XRD showed that with the addition of GNSs content, transmittances at 1373.4 cm −1 and 1454.4 cm −1 became smaller and the characteristic peak at 26.82° became stronger. TGA showed that the GNS/CF/PP composite can be used at high temperature below 456°C. Blending 10 wt% CFs and 10 wt% GNSs into the PP polymer resulted in excellent conductivity (0.397 S/cm), which indicated the occurrence of the critical percolation threshold phenomenon, and also reached the maximum electromagnetic shielding effectiveness (EMSE) of 20 dB at 1.28–2.00 GHz. Laminated with five layers of composites, its EMSE achieved 25–38 dB at 0.3–3.0 GHz, corresponding to blocking of 94.38–98.74% electromagnetic waves.